2023
DOI: 10.1021/acs.langmuir.2c02715
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir and Langmuir–Blodgett Films of Gold and Silver Nanoparticles

Abstract: Recently the focus of the Langmuir–Blodgett technique as a method of choice to transfer monolayers from the air/water interface onto solid substrates in a controllable fashion has been shifting toward purely hydrophobic gold and silver nanoparticles. The fundamental interactions between particles that become relevant in the absence of polar groups range from dispersive attractions from the metal cores and repulsions between ligand shells to weaker entropic factors. The layer evolution is explored, starting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…In this study, PDA nanovesicles were first prepared by functionalizing PDA with M149 antibody, and immobilization of these PDA nanovesicles on PVDF membrane showed a further improved stability and sample handling. However, currently conventional approaches for fabrication of solid-phase CP colorimetric biosensors have often relied on Langmuir–Blodgett (LB) or Langmuir–Schaeffer (LS) films [ 98 ]. These methods presented weak optical signals and required stringent conditions.…”
Section: Cps-based Optical Biosensors For Virus Detectionmentioning
confidence: 99%
“…In this study, PDA nanovesicles were first prepared by functionalizing PDA with M149 antibody, and immobilization of these PDA nanovesicles on PVDF membrane showed a further improved stability and sample handling. However, currently conventional approaches for fabrication of solid-phase CP colorimetric biosensors have often relied on Langmuir–Blodgett (LB) or Langmuir–Schaeffer (LS) films [ 98 ]. These methods presented weak optical signals and required stringent conditions.…”
Section: Cps-based Optical Biosensors For Virus Detectionmentioning
confidence: 99%
“…One approach used to resolve the aforementioned problem is the use of the Langmuir technique. This technique is widely known as the typical method for the fabrication of 2D assemblies to study the structures and properties of substances such as lipids, proteins, and NPs. However, the known concepts of Langmuir layer formation confirmed that layers consisting of metallic NPs show different types of interactions compared to those consisting of amphiphilic molecules. In the context of NPs, it requires the dispersion of NPs at the air–water interface, while the desired packing density, distribution, and interactions of NPs are controlled via surface pressure (π), which can be adjusted by pushing the Langmuir barriers toward each other.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been developed for the 2D self-assembly of NPs on a substrate surface, including Langmuir–Blodgett (L–B) deposition technique, which is commonly employed for two-dimensional (2D) self-assembly of hydrophobic organic ligand-coated NPs into a close-packed monolayer film at the air–water interface . Then, monolayers are transferred to the solid substrates using the classical Langmuir–Schaefer (L–S) method, where a hydrophobic surface, such as a carbon-coated transmission electron microscopy (TEM) grid, is horizontally touched to the monolayer of NPs to lift it. , However, this method is limited to hydrophobic surfaces, and a large area of the monolayer is often challenging to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant coating on these NPs creates a repulsion barrier that prevents their cores from agglomerating irreversibly. In the solution, there are two fundamental interactions between the particles: core–core attractions and ligand–ligand repulsions . This allows the NPs to modify their relative positions until they form a low-energy, self-organized pattern, such as 2D monolayers. , It is also investigated in one of the experiments using SNIFTIR spectra of Cit-Au-NPs (111) that, via COOH hydrogen bonds, the adsorbed citrate on the Au-NPs surface interacts with a different kind of citrate anion in the solution .…”
Section: Introductionmentioning
confidence: 99%